Function and Potentials of M. tuberculosis Epitopes - Ivanyi, Juraj (Frontiers in Immunology, 2014)
Study of the function of epitopes of Mycobacterium tuberculosis antigens contributed significantly toward better understanding of the immunopathogenesis and to efforts for improving infection and disease control. Characterization of genetically permissively presented immunodominant epitopes has implications for the evolution of the host-parasite relationship, development of immunodiagnostic tests and subunit prophylactic vaccines. Knowledge of the determinants of cross-sensitisation, relevant to other pathogenic or environmental mycobacteria and to host constituents has advanced. Epitope defined IFNγ assay kits became established for the specific detection of infection with tubercle bacilli both in humans and cattle. The CD4 T cell epitope repertoire was found to be more narrow in patients with active disease than in latently infected subjects. However, differential diagnosis of active TB could not be made reliably merely on the basis of epitope recognition. The mechanisms by which HLA polymorphism can influence the development of multibacillary tuberculosis need further analysis of epitopes, recognised by Th2 helper cells for B cell responses. Future vaccine development would benefit from better definition of protective epitopes and from improved construction and formulation of subunits with enhanced immunogenicity. Epitope defined serology, due to its operational advantages is suitable for active case finding in selected high disease incidence populations, aiming for an early detection of infectious cases and hence for reducing the transmission of infection. The existing knowledge of HLA class I binding epitopes could be the basis for the construction of T cell receptor like ligands for immunotherapeutic application. Continued analysis of the functions of mycobacterial epitopes, recognised by T cells and antibodies, remains a fertile avenue in tuberculosis research.